2016
DOI: 10.1038/srep39797
|View full text |Cite
|
Sign up to set email alerts
|

Multi-InDel Analysis for Ancestry Inference of Sub-Populations in China

Abstract: Ancestry inference is of great interest in diverse areas of scientific researches, including the forensic biology, medical genetics and anthropology. Various methods have been published for distinguishing populations. However, few reports refer to sub-populations (like ethnic groups) within Asian populations for the limitation of markers. Several InDel loci located very tightly in physical positions were treated as one marker by us, which is multi-InDel. The multi-InDel shows potential as Ancestry Inference Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…However, the higher combined indexes of MEC Krüger and MEC Desmarais Duo are observed according to the genetic polymorphisms of haplotype. Our findings combined with our previous investigations 27 29 indicate that the 19 X-STRs are informative and polymorphic in Chinese Gelao population and this amplification system can efficiently complement the analyses of autosomal 13 , mitochondrial and Y-chromosomal STRs 16 , single nucleotide polymorphisms (SNPs) 62 , insertion/deletions (InDels) 63 in the forensic applications, especially in some special and complicated kinship cases (deficiency kinships cases of paternal grandmother/granddaughter duos, mother-son duos, and full or half-sibling duos involving two females, as well as some specific incest cases).…”
Section: Discussionsupporting
confidence: 65%
“…However, the higher combined indexes of MEC Krüger and MEC Desmarais Duo are observed according to the genetic polymorphisms of haplotype. Our findings combined with our previous investigations 27 29 indicate that the 19 X-STRs are informative and polymorphic in Chinese Gelao population and this amplification system can efficiently complement the analyses of autosomal 13 , mitochondrial and Y-chromosomal STRs 16 , single nucleotide polymorphisms (SNPs) 62 , insertion/deletions (InDels) 63 in the forensic applications, especially in some special and complicated kinship cases (deficiency kinships cases of paternal grandmother/granddaughter duos, mother-son duos, and full or half-sibling duos involving two females, as well as some specific incest cases).…”
Section: Discussionsupporting
confidence: 65%
“…Previous anthropological and genetic studies have provided evidences that the peopling of China is characterized by different ancestral ethnicity origin by maternal lineages (mitochondrial genome) and paternal genetic signatures (Y-Chromosome) 42 48 . Despite these large-scale efforts in investigating patterns of natural selection, estimating individual ancestry and predicting the evolutionary history in Chinese populations based on SNPs, InDels, and CODIS STR loci 21 23 , 49 , 50 . The human genetic variation of non-CODIS STRs in the Sichuan Yi and Tibetan populations remains unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been proved that the InDels could be useful in human identification ( Pereira et al, 2009 ), mixed stain identification and deconvolution ( Oldoni et al, 2017 ), as well as population genetic analysis including biogeographic ancestry inference and population substructure determination ( Santos et al, 2010 ). Sun et al (2016) verified the considerable potency of a multi-InDel panel in ancestry inference of subpopulations in China and Caputo et al (2017) reported the potential use of a 33 X-InDel panel in Argentina populations. A year later, Hwa et al (2018) also reported a panel’s efficiency in degraded and non-degraded DNA mixtures with SNPs and InDels simultaneous analyzed via MPS technology.…”
Section: Introductionmentioning
confidence: 72%